Basic characterization of antibodies targeting receptors of the tumor necrosis factor receptor superfamily - Zaitseva, Olena; Anany, Mohamed; Wajant, Harald; Lang, Isabell (Frontiers in Immunology, 2023)
Many new immunotherapeutic approaches aim on the stimulatory targeting of receptors of the tumor necrosis factor (TNF) receptor superfamily (TNFRSF) using antibodies with intrinsic or conditional agonism. There is an initial need to characterize corresponding TNFRSF receptor (TNFR)-targeting antibodies with respect to affinity, ligand binding, receptor activation and the epitope recognized. Here, we report a collection of simple and matched protocols enabling the detailed investigation of these aspects by help of Gaussia princeps luciferase (GpL) fusion proteins and analysis of interleukin-8 (IL8) production as an easily measurable readout of TNFR activation. In a first step, the antibodies and antibody variants of interest are transiently expressed in human embryonal kidney 293 cells, either in non-modified form or as fusion proteins with GpL as a reporter domain. The supernatants containing the antibody-GpL fusion proteins can then be used without further purification in cell-free and/or cellular binding studies to determine affinity. Similarly, binding studies with mutated TNFR variants enable the characterization of the antibody binding site within the TNFR ectodomain. Furthermore, in cellular binding studies with GpL fusion proteins of soluble TNFL molecules, the ability of the non-modified antibody variants to interfere with TNFL-TNFR interaction can be analyzed. Last but not least, we describe a protocol to determine the intrinsic and the Fc gamma receptor (FcγR)-dependent agonism of anti-TNFR antibodies which exploits i) the capability of TNFRs to trigger IL8 production in tumor cell lines lacking expression of FcγRs and ii) vector- and FcγR-transfected cells, which produce no or only very low amounts of human IL8. The presented protocols only require standard molecular biological equipment, eukaryotic cell culture and plate readers for the quantification of luminescent and colorimetric signals.